In Order To Ensure The Right To A Building That Has Expired, The Cessie Recipient Must Provide Legal Notice In Light Of The Cessie Act. - Rochma, Ainur (Universitas Islam Malang, 2024)
Abstract : Execution of this credit could have obstacles. For example, a debtor commits a default that leads to credit clogging. However, banks or creditors have found a way to solve the credit crash. There are two (two) ways to solve a problem credit: saving credit and settling credit. One of the ways that banks are defeating credit blocks is through debt billing redirection, commonly called a cessie. A legal question arises regarding a cessation act made by a notary, namely that the guarantee applied to that act has expired. The question is: what are the legal consequences for the recipient of the cessie against the act of the cessie with the object of guaranteeing the right of possession of the certificate of right of use of the building that has expired its term, and how can legal action be taken by the reciprocator of the cessie against an act of cessie with the object of guaranteeing the right to possession of the building's right of usage that has expired its term. In writing this thesis, the researcher uses normative research methods. As for the results of the legal investigation of the cessioner against the cessie act with the object of the security of the right of use of the building that has expired its term, the act is still considered valid and the new creditor still acquires the right to the account but cannot be granted the right for the building to be secured by the new creditors and can not be registered such object of security to the land office due to the expiry of the time period of the rights of use such building as well as the legal effort that can be made by the recipient of the cessie against the act of cession with the objects of the guarantee of the Right of Use of the Building Certificate of Use which has exceeded its term is negotiated against the old creditor concerning the said act of cesie by asking the liability to the old creditors to renew or extend the time of the construction rights that have expended its term.